A virtual fields method for identifying anisotropic elastic constants of fiber reinforced composites using a single tension test: Theory and validation. (1st November 2020) - Kim, Chanyang; Kim, Jin-Hwan; Lee, Myoung-Gyu
Abstract: A novel inverse identification method using only a single tensile specimen for obtaining four anisotropic elastic constants of fiber reinforced composites sheet is proposed in this study. The method is based on virtual fields method (VFM) for solving weak form equilibrium equation with an optimized tension-type non-standard specimen specially designed with an elliptic hole at the center of the specimen (though not limited to this special shape). Full-field strain measured by a digital image correlation (DIC) technique is applied as experimental strain fields which are used as inputs of the VFM. For optimizing the tension-type VFM specimen, finite element (FE) analysis is conducted as a virtual experiment to generate ideal strain fields. The determined tension-type VFM specimen has an elliptic hole with 45° inclined to the loading direction, which is optimized from the error analysis between the FE input and VFM calculated material constants. For the validation of the proposed approach, experiments are performed with unidirectional carbon fiber reinforced plastic (UD-CFRP) sheets. The comparison of VFM identified anisotropic constants to those determined from the standard tensile tests with three different orientated samples shows satisfactory accuracy ranging between −5.94 and 0.71%, errors which confirm the validity of the new inverse method for the characterization of anisotropic elasticity of composites sheets. Graphical abstract: Image 1 Highlights: An inverse engineering method, or a virtual fields method, is proposed to identify anisotropic constants of composites. A special VFM specimen is designed based on a uniaxial tension sample with an elliptic hole at the center. The VFM with an optimized tensile specimen uses only single tensile test to obtain four anisotropic constants of composites. The material constants identified by VFM are reliable within error range of 5.94 to 0.71 %.